A hypervelocity impact facility optimised for the dynamic study of high pressure shock compression. (2017) - Ringrose, T.J.; Doyle, H.W.; Foster, P.S.; Betney, M.; Skidmore, J.W.; Edwards, T.; Tully, B.; Parkin, J.R.; Hawker, N.
Abstract: This paper describes the installation and subsequent commissioning of a 7.5 km s -1, 12.7 mm bore two-stage light gas gun facility, based at First Light Fusion, Oxford, UK. The unique modular design of the diagnostics and impact chamber provides a flexible platform for a wide range of interdisciplinary hypervelocity impact studies. To validate the facility, results are shown for two high pressure shock compression experiments. First, measurements of shock propagation in PMMA are compared to tabulated equation of state data [1], over the impact velocity range 1.6 to 7.5 km s -1 . Second, measurements of jet formation from open-backed cavity targets are compared to simulation results from a front-tracking hydro code, Hytrac.